Predictive Value of Red Cell Distribution Width-to-Platelet Ratio Combined with Procalcitonin in 28-day Mortality for Patients with Sepsis - Ying Si; Bo Sun; Yongmao Huang; Ke Xiao (Critical Care Research and Practice)
Objectives. The objective of this study was to investigate the predictive value of erythrocyte distribution width-to-platelet ratio (RPR) combined with procalcitonin (PCT) on 28-day mortality in patients with sepsis. Methods. A total of 193 patients with sepsis admitted to the Affiliated Hospital of Southwest Medical University from January 2013 to January 2018 were selected as the study objects. Univariate and multivariate analyses were used to understand the indicators related to the 28-day prognosis of patients, and the ROC curve was further drawn. The Kaplan–Meier curve was used to evaluate the prognosis of patients. Results. A total of 193 patients were enrolled and divided into the survivor group (=156) and nonsurvivor group (=37) according to the prognosis within 28 days. The median age was 62.5 years, and 64.7% were males. Multivariate analysis showed that PCT and RPR were independent risk factors for 28-day prognosis in sepsis patients. The area under the ROC curve of PCT and RPR were 0.894 and 0.861, respectively, and the cutoff values were 27.04 and 0.12, respectively. Survival curve analysis showed that PCT and RPR were associated with the 28-day prognosis of patients, and the combination of PCT and RPR had a better predictive effect. Conclusions. PCT and RPR are independent predictors of sepsis prognosis. The combined application of PCT and RPR (PCT-RPR) can further improve the predictive performance and provide a reference for the clinical diagnosis, treatment, and prognosis evaluation of sepsis patients.